Delayed diagnosis: An important prognostic factor for oesophageal atresia in developing countries - Karakus, Suleyman Cuneyt; Ozokutan, Bulent Hayri; Bakal, Unal; Ceylan, Haluk; Sarac, Mehmet; Kul, Seval; Kazez, Ahmet (Wiley-Blackwell, 2016)
Aim: The aim of this study is to analyse the effect of delayed diagnosis on mortality rates, and evaluate the role of delayed diagnosis as a new prognostic factor in patients with oesophageal atresia (OA), especially in developing countries. Methods: The records of 80 consecutive patients with OA (2008-2013) were reviewed. Patients were divided into two groups according to the time of diagnosis. As we demonstrated the effect of delayed diagnosis on mortality, we decided to develop a new classification that will be utilised to predict the prognosis of OA. The discrimination ability of the new prognostic classification was compared with those of the Waterston, Montreal and Spitz classifications using the area under the curve. Results: The parameters of the new prognostic classification were birth weight less than 2000 g, the presence of major cardiac/life-threatening anomalies and delay in diagnosis. Class I consisted of patients with none or one of these parameters. Class II consisted of patients with two or three of these parameters. The area under the curve of the new classification was better than those of the other classifications in determining the prognosis of patients with OA. Conclusions: Delayed diagnosis of OA significantly led to morbidity and mortality. Although delayed diagnosis is not a characteristic of newborn or a marker of severity for OA and is a health care system issue in developing countries, we here point out that it is a prognostic factor in its own right. Our new classification has a superior discriminatory ability compared to the above-mentioned classifications.
Keywords: health policy; oesophageal congenital anomalies; oesophageal surgery; outcomes